Students’ Satisfaction On Using Whatsapp For Online Learning At The Fifth Semester Students Of English Education Program In IAIN Bukittinggi - Saroh, Mai; Arifmiboy, Arifmiboy (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2022)
This research is motivated by differences in views regarding the satisfaction of using the WhatsApp for online learning in IAIN Bukittinggi. Some of the problems that exist in IAIN Bukittinggi include dissatisfaction with the purpose of learning to use WhatsApp, during the teaching and learning process the features of the WhatsApp application do not support due to disruption of the internet network. Thus, students in the English education program in Bukittinggi who initially studied directly in the classroom had to switch to the WhatsApp application which was used as a medium for online learning during the Covid-19 pandemic. This research was conducted to find out how the satisfaction level of classes A, B, C at the fifth-semester students in the English education program in IAIN Bukittinggi for online learning is. The design of this research was a survey, and the instrument used is a questionnaire. The subjects of this research were students of classes A, B, and C with a total of 90 students and students who will be used as research samples as many as 90 students. The instrument validity test was carried out by distributing instruments to four experts as instrument validators and analyzing the data using quantitative descriptive techniques with percentages. Based on the results of research conducted by the researcher, the title of this research is the students’ satisfaction with using WhatsApp for online learning in the English education program in IAIN Bukittinggi. The researcher conducted research to determine how the level of students' satisfaction in learning English with the objectives and utilization of the WhatsApp features. The result showed that the level of students' satisfaction with the learning objectives is 54%. It means that quite satisfied based on the data interpretation that has been determined. While the use of the WhatsApp feature is 66,5%. It means that satisfied. Thus, students had a positive attitude towards using WhatsApp for online learning. In light of the findings of the study, it is quite recommended that lecturers should use learning classes that use WhatsApp as a learning platform during the Covid-19 pandemic.